Towards Generalizing Visual Process Patterns - Soltenborn, Christian; Engels, Gregor (Electronic Communications of the EASST, 2010)
Visual Process Patterns (VPP) is a visual language to describe constraints on the behavior of UML Activities. They have been developed for the sake of formulating and verifying requirements on business process models in a visual, intuitive way (with UML Activities being one possible description language). In the VPP approach, a visual process pattern is translated into an LTL formula, which can then be verified against a transition system describing the behavior of the Activity under consideration. In this paper, we aim at generalizing VPP. We show how to formulate patterns more generally, using an enhanced version of the concrete syntax of the behavioral model under consideration. Additionally, we describe how these more general patterns can be verified against a modelâs behavior.